Deconstructing Dr. Strangelove : the secret history of nuclear war films - Maloney, Sean M., 1967- (Potomac Books, an imprint of the University of Nebraska Press, 2020)
"'Deconstructing Dr. Strangelove' examines how well the Cold War crisis films stack up against historical reality, or at least as much of that reality as we can reconstruct with confidence"-- Provided by publisher
Keywords: Nuclear warfare in motion pictures.; Cold War in motion pictures.; War films -- History and criticism.; Guerre nucléaire au cinéma.; Guerre froide au cinéma.; Films de guerre -- Histoire et critique.; Cold War (1945-1989) in motion pictures; Nuclear warfare in motion pictures; War films; Criticism, interpretation, etc.